The rise of politically motivated cyber attacks: actors, attacks and cybersecurity - Munk, Tine (Routledge studies in crime and society, 2022)
The growing online threat. The actors -- Cyber attacks, means and methods -- Cybersecurity and strategies -- Cyberwar and warfare: state and state-sponsored attacks -- Cyberterrorism and ransomware: state-supported groups -- Other politically motivated attacks: political activists and hacktivists.